A VARIETY OF TEACHING-LEARNING STRATEGIES TO IMPROVE THE CARING BEHAVIOR OF NURSING STUDENTS - Anastasia Anna; Aan Nuraeni; Atlastieka Praptiwi (Belitung Nursing Journal, 2018)
Background: Caring is the essence of nursing that is believed vital in improving the health and well-being of patients and in facilitating health promotion. Nursing education has a fundamental role in shaping a positive student’s caring behavior. Objective: This study identified the caring behavior of the final-year nursing students after completing a critical care nursing course unit by implementing assorted teaching-learning strategies. Methods: This study was a descriptive research using a comparative design. Samples were recruited from a group of 152 final-year students using a random sampling technique (n=76). Data were collected using a valid and reliable Indonesian caring instrument consisting of 32 items based on Watson’s ten carative factors. Data were analyzed using descriptive statistics by calculating mean scores of students’ caring behavior. A paired t test was performed to evaluate the difference between caring behavior before and after completion of the course unit involving a diverse teaching learning strategy, such as face-to-face lectures in the class, quizzes and practicums, facilitated small group case-based discussions, and expert reviews. Results: Results showed that more than half of the students had negative caring behavior before (59.22%) and after (54.55%) participating in learning process. There was also a barely statistical insignificance in the change of caring behavior following the course unit that involved various learning strategies (p value = 0.276). Further analyses of the 10 carative factors revealed that there was a significant change in transpersonal teaching-learning, provision for a supportive, protective, and/or corrective mental, physical, sociocultural, and spiritual environment, and spiritual environment and existential-phenomenological spiritual forces (improved, p value <0.05). Conclusions: Student-centered learning is a good approach to enhance the students’ critical thinking skills. However, in implementing the approach, there is a need to reevaluate appropriate method so as to simultaneously develop students’ critical thinking skills, caring behavior, and empathy.